In the days of our grandmothers: a reader in Aboriginal women's history in Canada - Kelm, Mary-Ellen; Townsend, Lorna (University of Toronto Press, 2006)
From Ellen Gabriel to Tantoo Cardinal, many of the faces of Aboriginal people in the media today are women. In the Days of Our Grandmothers is a collection of essays detailing how Aboriginal women have found their voice in Canadian society over the past three centuries. Collected in one volume for the first time, these essays critically situate Aboriginal women in the fur trade, missions, labour and the economy, the law, sexuality, and the politics of representation. (Midwest).
Section: xi, 434 pages : illustrations, cartes ; 24 cm
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; commerce; commerce de peaux; cours; discipline; droit; droits des femmes*; droits des femmes* autochtones; famille; féminisme autochtone; histoire; histoire et politique; pol4105; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sexualité; thématiques; travail

Stolen From Our Bodies: First Nations Two-Spirits/Queers and the Journey to a Sovereign Erotic - Driskill, Qwo-Li (Studies in American Indian Literatures, 2004)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; autothéorie; cherokee; cours; discipline; féminisme autochtone; militance; premier cycle; premières nations; périodes historiques; queer; régions géographiques; sexualité; soc2014; système colonial; systèmes d'oppressions; thématiques; états-unis